Effects of rape/common vetch intercropping on biomass, soil characteristics, and microbial community diversity - Qu, Jiahui; Li, Lijun; Wang, Ying; Yang, Jinhu; Zhao, Xinyao (Frontiers in Environmental Science, 2022)
Legume-brassica intercropping has been widely used to increase productivity in modern sustainable agricultural systems. However, there has been few studies of assessing the linkages of soil properties and soil microorganisms. Soil microorganisms play a key role in soil nutrient turnover and plant community composition. To elucidate the response of the soil microbial community diversity and structure to intercropping. We conducted a 2-year experiment based on soled common vetch (CV), soled rape (R), and common vetch-rape intercropping (IRCV) with phosphorus (P) addition in alkaline soil. The microbial communities of bacteria and fungi in the rhizosphere soil were examined based on high-throughput sequencing targeting the 16S rRNA and ITS genes, respectively. In addition, we analyzed the changes of soil properties and enzyme activities. Intercropping significantly increased dry matter (up to 98.86% and 81.48%, respectively) compared to soled common vetch. Intercropping decreased soil bulk density and pH. Soil nutrient contents and enzyme activities were higher under intercropping patterns. However, bacterial alpha diversity was higher under monocropping. In addition, Soil dominant bacterial phyla Proteobacteria, Gemmatimonadetes, Bacteroidetes, and Rokubacteria presented higher abundance in IRCV relative to those in CV and R, but phyla Chloroflexi decreased significantly in IRCV than the other two treatments. The redundant analysis showed that soil organic matter and available phosphorus were positively correlated with the dominant flora of bacteria and fungi. Common vetch-rape intercropping attained higher biomass and altered soil microbial community composition as well as soil properties. The results of the present study concluded some interesting facts of intercropping systems that positively improved the soil microbial activity and this kind of strategy could help to cultivate multiple crops to improve the soil properties by sustainable production.